2016
DOI: 10.1111/jace.14491
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Properties of ZnO Films on the Efficiency of Planar ZnO/Perovskite/P3HT Solar Cell

Abstract: ZnO thin films prepared by pulsed laser deposition at low temperature are utilized as the electron transport layer in CH3NH3PbI3−xClx‐based perovskite solar cells with a planar heterojunction structure. Oxygen pressure greatly influences the transparent and conductive properties of ZnO films, which are extremely important as electron transport layer for the perovskite solar cells. The transparent and conductive properties of the films under different oxygen pressures are studied by ultraviolet‐visible spectrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…3 Meanwhile, other HTL materials have been used to achieve over 10% efficiencies (e.g. PTAA, 29,66,68 P3HT, [69][70][71] PEDOT:PSS, 60,61,72 CuSCN, 73,74 triazine-Th-OMeTPA, 75 PVCz-OMeDAD, 76 OMeTPA-BDT, 77 NiO x , 56,64,78,79 CuGaO 2 , 54 X26, 80 X36, 80 NiMgLiO 41 etc.). Carbon materials, [81][82][83][84][85] aluminum, 34,56,61,62 silver, 64,65,86 and gold [87][88][89][90] have been used as electrode.…”
Section: Typical Pscs Structurementioning
confidence: 99%
See 1 more Smart Citation
“…3 Meanwhile, other HTL materials have been used to achieve over 10% efficiencies (e.g. PTAA, 29,66,68 P3HT, [69][70][71] PEDOT:PSS, 60,61,72 CuSCN, 73,74 triazine-Th-OMeTPA, 75 PVCz-OMeDAD, 76 OMeTPA-BDT, 77 NiO x , 56,64,78,79 CuGaO 2 , 54 X26, 80 X36, 80 NiMgLiO 41 etc.). Carbon materials, [81][82][83][84][85] aluminum, 34,56,61,62 silver, 64,65,86 and gold [87][88][89][90] have been used as electrode.…”
Section: Typical Pscs Structurementioning
confidence: 99%
“… 3 Meanwhile, other HTL materials have been used to achieve over 10% efficiencies ( e.g. PTAA, 29,66,68 P3HT, 69–71 PEDOT:PSS, 60,61,72 CuSCN, 73,74 triazine-Th-OMeTPA, 75 PVCz-OMeDAD, 76 OMeTPA-BDT, 77 NiO x , 56,64,78,79 CuGaO 2 , 54 X26, 80 X36, 80 NiMgLiO 41 etc. ).…”
Section: Perovskite Structure and Typical Pscs Structurementioning
confidence: 99%
“…In contrast, the solution-processible ETL based on ZnO nanoparticles can provide enough conductivity without using a high-temperature sintering process. 13,14 It is now also shown that a ZnO-based ETL may have a favorable conduction band energy level to perovskite-type solids, 15 higher electron mobility, 16 and outstanding optical transparency in the visible spectral range. 17 In addition, planar devices can reduce the absorption path length and make it possible for photo-excitation to take place deep into the material, while the mesoporous devices generate most charge carriers relatively close to the junction under strong light-scattering conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 43 ] It can be seen that N‐M‐TiO 2 and M‐TiO 2 exhibit similar UV light absorption range of 190–400 nm, which contributes to the light stability of perovskite in PSCs. [ 44 ] Different crystalline phases with different Fermi energy levels possibly change the WF of TiO 2 . [ 45 ] To study this, the WFs of N‐M‐TiO 2 and M‐TiO 2 films were measured in air by using a Kelvin probe (surface scanning: 4.17 × 4.17 mm).…”
Section: Resultsmentioning
confidence: 99%